Energy Cane as a Feedstock for Biofuel Industries opportunities and challenges - Govindaraj, P (Indian Farming, 2017)
Energy cane has large potential to ensure continuous supply of raw materials for biofuel industries throughout the year. The energy need of the country is expected to be more than 200% during 2030. In addition, India’s economy is rural based and one of the developmental parameter is the availability of power. It is estimated that establishment of 10MW/hr power industry requires about 700 of bagasse with 50% moisture per day. This power plant requires 3,700 ha of energy cane plantation with average harvestable biomass potential of 150 t/ha for uninterrupted supply of feedstock throughout the year. The power generated from this plant will be sufficient to cater the agriculture, domestic need and to support local agro based industries for a cluster of villages. This will improve the standard of living of the rural farmers and ensure the economic empowerment.